2003
DOI: 10.1080/01448765.2003.9755278
|View full text |Cite
|
Sign up to set email alerts
|

Tradition, Dynamics and Sustainability of Plant Species Composition and Management in Homegardens on Organic and Non-Organic Small Scale Farms in Alpine Eastern Tyrol, Austria

Abstract: In Eastern Tyrol (Austria), homegardens are an integral part of the farming system. The aim of this paper is to present evidence for the development of gardening in the study area and to identify differences/similarities between gardens at organic and non-organic farms. In 1997 and 1998, in homegardens on 91 organic and 105 non-organic farms from 12 communities, occurrence and abundance of cultivated plant species were surveyed and interviews were carried out about garden history, management and plant use. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 15 publications
4
47
0
Order By: Relevance
“…Several studies showed that species diversity in a homestead garden can range from less than five [9][10][11][12] to more than 100 [13][14][15]. In Bangladesh, various studies, for example, [3,7,9,[16][17][18][19][20][21][22][23] explore the floristic composition (mainly trees) in the homestead gardens; homestead agroforestry system by [24][25][26]; homestead plantation and traditional uses by [27,28]; quantitative structure and silvicultural management by [29][30][31]; production and services by [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that species diversity in a homestead garden can range from less than five [9][10][11][12] to more than 100 [13][14][15]. In Bangladesh, various studies, for example, [3,7,9,[16][17][18][19][20][21][22][23] explore the floristic composition (mainly trees) in the homestead gardens; homestead agroforestry system by [24][25][26]; homestead plantation and traditional uses by [27,28]; quantitative structure and silvicultural management by [29][30][31]; production and services by [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Much ethnobotanical research on homegardens is still carried out among the indigenous peoples of the tropical developing world (see Millat-e-Mustafa 1996 for a review of homegarden research). This research has led to interesting results and new insights into the composition, management, and importance of these agroecosystems for subsistence and cash income, the application of tradi-To enhance ethnobotanical research on homegardens and to encourage a discussion of scientific methodology, we present here the tools and methods we have used to collect data while studying homegardens of Ch'ol and Tzeltal migrants of Lowland Chiapas in Mexico (Vogl 1998;Vogl, VoglLukasser, and Caballero 2002) and of Eastern Tyrolean farmers in Austria Vogl-Lukasser, Vogl, and BolharNordenkampf 2002;Vogl and Vogl-Lukasser 2004), and in Kalimantan, Indonesia (Puri 1997(Puri , 2001Sheil et al 2002).…”
mentioning
confidence: 99%
“…The study of the turnip began with the broader ethnobotanical study between 1997 and 1998 where 196 home gardens on farms from 12 communities in Eastern Tyrol were investigated (Vogl et al 2004, Vogl & Vogl-Lukasser 2003, Vogl-Lukasser & Vogl 2002, 2005. In this inventory, 16 women farmers were found who grew turnip either in their gardens or as field vegetable in arable plots near their homesteads.…”
Section: Ethnobotanical Inventorymentioning
confidence: 99%